Synthesis of fluorescent bisboronic acid sensors and their recognition of mono-/oligo-saccharides - Wang, Yan-En; Rong, Rui-Xue; Chen, Hua; Zhu, Meng-Yuan; Wang, Bing-He; Li, Xiao-Liu (Chinese chemical letters, 2017)
Sensors capable of recognizing cell surface carbohydrates,such as sialyl Lewis X（sLe-x）,are invaluable research tools and for the diagnosis and early detection of many forms of cancer.In this paper,we report the design and synthesis of a series of bisboronic acids 6（a-f） as fluorescent sensors towards mono-/oligosaccharides.Among them,compounds 6d and 6e showed strong binding affinities with glucose and fructose,while compound 6c,in which two anthracene-based boronic acid units were linked by a hexamethylene spacer,was able to recognize sLe-x selectivity and stained HEPG2 cells at 1 μmoI/L.